Gamification in Workshop - Sadiku, Matthew N. O.; Chukwu, Uwakwe C.; Sadiku, Janet O. (Research Parks Publishing LLC, 2023)
Gamification is the process of adding elements of games to non-game activities. It is a popular approach to making customer experiences more engaging and fun. It is now reaching the workplace. Gamification workplace is the use of game techniques in the work environment. In the workplace, gamification can encourage employee engagement, gratification, and retention. Gamification introduces a competitive element to employees’ tasks, using rewards to give them a greater incentive to meet company goals. This paper provides an overview on gamification workplace with examples.